2022
DOI: 10.1155/2022/4903265
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Acupuncture Combined with Aerobic Exercise for Coronary Heart Disease as Cardiac Rehabilitation

Abstract: Background. The mortality of coronary heart disease continues to rise. Cardiac rehabilitation intervenes the risk factors of cardiovascular disease, improves cardiopulmonary function, maintains healthy psychology, improves the quality of life of patients, and reduces cardiovascular mortality. Objective. To explore the effect of acupuncture combined with aerobic exercise on cardiopulmonary exercise ability, blood lipid, fatty acid oxidation, and psychology in patients with coronary heart disease. Methods. Sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[ 32 ] The effect of different exercise types on CHD patients is another hotspot in this field. Acupuncture combined with aerobic exercise has a positive impact on cardiopulmonary capacity, blood lipids, fatty acid oxidation and psychology in CHD patients, [ 33 ] while extracorporeal anti-bo combined with high-intensity aerobic exercise significantly reduced the incidence of major postoperative adverse cardiovascular events and postoperative activities in PCI patients and improved their daily living ability. [ 34 ] Regarding the most effective types of exercise, studies have shown that a combination of aerobic, resistance, breathing or inspiratory muscle training has the best results in improving aerobic capacity, muscle strength, functional capacity, ventilatory response and quality of life in cardiovascular patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ] The effect of different exercise types on CHD patients is another hotspot in this field. Acupuncture combined with aerobic exercise has a positive impact on cardiopulmonary capacity, blood lipids, fatty acid oxidation and psychology in CHD patients, [ 33 ] while extracorporeal anti-bo combined with high-intensity aerobic exercise significantly reduced the incidence of major postoperative adverse cardiovascular events and postoperative activities in PCI patients and improved their daily living ability. [ 34 ] Regarding the most effective types of exercise, studies have shown that a combination of aerobic, resistance, breathing or inspiratory muscle training has the best results in improving aerobic capacity, muscle strength, functional capacity, ventilatory response and quality of life in cardiovascular patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials should follow the gold standard of randomized, controlled, blinded, and repetitive design, overcome subjective bias as much as possible, and explore multi-center, multi-perspective, multi-method, multi-level, and multi-dimensionally, to fully confirm the advantages of acupuncture in treating MP, and to better serve the patients. [73][74][75][76] In summary, this paper analyzes the evolution of acupuncture therapy for MP research, which helps to clearly show the overall situation of acupuncture therapy for MP, with a view to providing certain reference value for in-depth research and future selection of topics in this field. Of course, CiteSpace software has more data analysis functions, which are not all used in this paper, and it is worthwhile to conduct in-depth research in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “The Effect of Acupuncture Combined with Aerobic Exercise for Coronary Heart Disease as Cardiac Rehabilitation” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%